1994
DOI: 10.1002/hep.1840200436
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Protein Kinase C and Cytosolic Ca2+ on Exocytosis in the Isolated Perfused Rat Liver

Abstract: Both protein kinase C and cytosolic Ca2+ are involved in the regulation of exocytosis in a number of cell types. However, the relative importance of each of these for apical exocytosis in the hepatocyte is unknown. To investigate this, we studied the effects of protein kinase C and Ca2+ agonists on horseradish peroxidase excretion in the isolated perfused rat liver. Vasopressin increased both horseradish peroxidase concentration and net horseradish peroxidase excretion in bile, and these effects were abolished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…25 Therefore it can be speculated that the balance between different activated PKC isoforms influence the resulting effect on bile flow. Cholestatic effects of PKC activators involve impaired apical exocytosis 26 and reduced sinusoidal bile acid uptake. 27 In human HepG2 hepatoblastoma cells PKC activation reduces the delivery of sphingolipids to the canalicular membrane.…”
mentioning
confidence: 99%
“…25 Therefore it can be speculated that the balance between different activated PKC isoforms influence the resulting effect on bile flow. Cholestatic effects of PKC activators involve impaired apical exocytosis 26 and reduced sinusoidal bile acid uptake. 27 In human HepG2 hepatoblastoma cells PKC activation reduces the delivery of sphingolipids to the canalicular membrane.…”
mentioning
confidence: 99%
“…The key importance of the [Ca 2ϩ ] i signal is clear from three biophysical observations: the fast GnRH-induced exocytosis is synchronous with each [Ca 2ϩ ] i rise; it can be blocked by loading Ca 2ϩ buffers into the cytoplasm; and in the absence of GnRH, exocytosis can be initiated within milliseconds by rapid stepwise increases of [Ca 2ϩ ] i using caged Ca 2ϩ compounds (6,7). Nevertheless, many laboratories have reported that agents that activate protein kinase C (PKC) or increase cellular cAMP can stimulate exocytosis in a variety of cell types (8)(9)(10)(11)(12)(13)(14)(15)(16). Indeed, numerous early papers reported that such agents stimulated secretion of LH from gonadotropes (2,(17)(18)(19)(20), and therefore PKC and cAMPdependent protein kinase were suggested as important for the action of the releasing hormone, a hypothesis that has remained controversial.…”
mentioning
confidence: 99%
“…41,[44][45][46] Furthermore, in addition to the effect on actin conformation, PKC activation was reported to induce changes in other major cytoskeletal elements such as intermediate filament proteins [47][48][49] and tubulin. 42 Finally, PKC was reported to have a role in hepatocyte apoptosis induced by a number of compounds such as the bile salt, glycochenodeoxycholate, 50 [2][3][4] Dissipation of osmotic gradients induced by an increase of ''leakiness'' of the paracellular barrier appears to play a key role in this phenomenon. Indeed, VP as well as a number of agents affecting Ca 2ϩ mobilization such as the Ca 2ϩ -ionophore, A23187, and the inhibitor of microsomal Ca 2ϩ sequestration, t-butyl-benzohydroquinone, were all shown to increase tightjunctional permeability in both isolated perfused rat liver 4,[7][8][9] and in isolated rat hepatocyte couplets.…”
Section: Discussionmentioning
confidence: 99%
“…42 Finally, PKC was reported to have a role in hepatocyte apoptosis induced by a number of compounds such as the bile salt, glycochenodeoxycholate, 50 [2][3][4] Dissipation of osmotic gradients induced by an increase of ''leakiness'' of the paracellular barrier appears to play a key role in this phenomenon. Indeed, VP as well as a number of agents affecting Ca 2ϩ mobilization such as the Ca 2ϩ -ionophore, A23187, and the inhibitor of microsomal Ca 2ϩ sequestration, t-butyl-benzohydroquinone, were all shown to increase tightjunctional permeability in both isolated perfused rat liver 4,[7][8][9] and in isolated rat hepatocyte couplets. [10][11][12] Finally, the finding that similar manipulations leading to [Ca 2ϩ ] cyt elevation induce bleb formation (see Table 2 and Nicotera, 25 Stone, 26,29 and Orrenius 52 ) leads to the proposal that Ca 2ϩ may be involved in the cytoskeletal alterations associated with bleb formation.…”
Section: Discussionmentioning
confidence: 99%